CDK5-dependent phosphorylation and nuclear translocation of TRIM59 promotes macroH2A1 ubiquitination and tumorigenicity - Youzhou Sang (Nature Portfolio, 2019)
CDK5 is known to drive glioblastoma tumorigenicity but the downstream molecular mechanism is unknown. Here, the authors show that CDK5 activates STAT3 signalling via the nuclear import of TRIM59, which leads to the degradation of the tumour suppressor macroH2A1.